Fiqh Al-Aqalliyat; Jurisprudence For Muslim Minorities As A Guide To Living In Non-Muslim Countries - Hilmi Ridho; Hamim Maftuh Elmy; Muhammad Sibawaihi (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: Being a Muslim who lives in a limited situation is not expected by anyone. However, the reality today is that many Muslims have begun to migrate from one Muslim-dominated area to another non-Muslim-dominated area, either for the sake of continuing their studies or working to support their families. The challenges faced by Muslims in Indonesia are not as complex as Muslims living in Western (non-Muslim) countries, where they are a minority group. They often face various challenges to practice their faith. It takes a full struggle to remain continuous in practicing the teachings of Islam. This paper wants to examine the challenges and problems of Muslim minorities living in Western countries. In addition, it wants to re-examine how the fiqh response provides a solution to the problems that befall Muslim minorities living amid a non-Muslim majority group. There should be someone who pays special attention to this minority problem. On that basis, contemporary scholars think that Muslim minorities get special treatment from the point of view of fiqh. This is because relying on classical fiqh will actually complicate the position of Muslims in Western countries. Therefore, a progressive solution is needed by compiling a new fiqh specifically for Muslim communities in Western countries, namely fiqh al-aqalliyat. Keywords: Minority Jurisprudence, Minority Muslims, and Non-Muslims. Abstrak: Menjadi seorang muslim yang hidup dalam situasi serba terbatas tidaklah diharapkan oleh siapapun. Namun, realitanya dewasa ini banyak sekali umat Islam yang mulai hijrah dari satu wilayah yang didominasi umat Islam ke wilayah lain yang didominasi non muslim, baik untuk kepentingan melanjutkan studi ataupun bekerja mencari nafkah keluarga. Tantangan yang dihadapi oleh umat Islam yang ada di Negara Indonesia tidaklah serumit umat Islam yang hidup di Negara Barat (non muslim), di mana mereka menjadi kelompok minoritas. Mereka sering kali menghadapi berbagai macam tantangan untuk menjalankan keyakinannya. Butuh perjuangan penuh untuk tetap kontinu dalam menjalankan ajaran agama Islam. Tulisan ini ingin mengkaji tentang tantangan dan persoalan muslim minoritas yang menjalani kehidupan di Negara Barat. Selain itu, ingin menelaah kembali bagaimana respons fikih memberikan solusi atas persoalan yang menimpa muslim minoritas yang hidup di tengah-tengah kelompok mayoritas non muslim. Sudah semestinya harus ada orang yang memberikan perhatian khusus terhadap problem minoritas yang demikian ini. Atas dasar itu, para ulama kontemporer berpikir agar muslim minoritas mendapatkan penanganan khusus dari sudut pandang fikih. Sebab, bertumpu pada fikih klasik justru akan merepotkan posisi umat Islam di Negara Barat. Karenanya, dibutuhkan solusi progresif dengan menyusun fikih baru khusus komunitas muslim di Negara Barat, yaitu fiqh al-aqalliyat. Kata Kunci: Fikih Minoritas, Muslim Minoritas, dan Non Muslim.